A federal Republic of China: The road not taken - Lee, Byung Ho (International Journal of China Studies, 2019)
This paper explores the position of the Chinese Communist Party on federalism and ethnic self-government from 1922 to the present in historical and comparative perspectives. Its initial blueprint of a Federal Republic of China became a path not taken; however, the road to establishing a unitary multiethnic state for the future of China was neither inevitable nor accidental. This argument is developed and illustrated through comparing the pre-1949 and post-1949 periods, paying particular attention to the period of 1945-1954. The founding of a unitary state with regional autonomy while rejecting the Soviet ethnofederalism reveals Mao Zedong’s own autonomy vis-à-vis Stalin. The Chinese state since 1997 has carried out a kind of federalist experiment to a lesser extent, which can be perceived as a partial resurrection of an old Party line abandoned six decades ago.
Keywords: Chinese Communist Party; Federation; Minority nationality; Regional autonomy; United Front